(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Background: Osteoarthritis is the most common chronic inflammatory musculoskeletal condition in older people. It’s a major cause of disability in elderly populations around the world, particularly in developed countries. Objective: The objective study was to assess the quality of life in Osteoarthritis patients by using adaptive SF-36 questionnaire form based on their physical and mental status. Methods: A prospective observational study conducted in both the outpatient and inpatient department of orthopaedics at the primary care hospital, Rajahmundry, Andhra Pradesh. An adaptive SF-36 questionnaire form was used which consists of 36 questions of 8 subscales in that, 4 sub-scales assess physical status and remaining 4 sub-scales assess the mental status of osteoarthritis patients to determine the quality of the life. Results: A total of 108 patients were screened for assessing QOL in OA. Among them, 55.6% of males are affected by OA more than 44.4% of females. A total of 39 (51-60 years of patients) 53.97% women’s detect worse health than men, based on their PCS and MCS. Conclusion: We assessed QOL in osteoarthritis patients based on their physical and mental status questions (sub-scales) in adoptive SF-36 Questionnaire form. Our study concludes that women’s health is in worse condition at the age of 51-60 than men.